Hygiene and microbial contamination along the pork value chain in Vietnam - Sinh Dang Xuan; Hung Nguyen-Viet; Phuc Pham Duc; Ngan Tran Thi; Thanh Nguyen Tien; Unger, Fred; Makita, K.; Grace, Delia (Hanoi School of Public Health, 2015)
In Vietnam, pork accounts for 75% of total meat consumed daily at households. However, pork may contain high levels of microbial contamination such as Salmonella and Escherichia coli which might cause harm to consumers. To determine microbial contamination along the pork value chain, we collected 216 samples from 72 pig farms (floor swab, drinking and waste water), 545 from 49 slaughterhouses (carcass swab, lymph node, rectal feces, floor swab and washing water) and 514 from 220 pork shops in the informal markets (pork cuts, ground pork and cutting board swab) in two provinces of Vietnam (Hung Yen and Nghe An). Samples were analyzed to detect qualitatively and quantitatively Salmonella and E. coli. Overall prevalence of Salmonella combined from all types of above mentioned samples at pig farms, slaughterhouses and pork shops were 35%, 30% and 37%, respectively. Salmonella contamination in the final product (pork at market) was 45% and an average concentration of 9 MPN/g was recorded. E. coli average load along different points of the chain was 5.3 ± 1.4 (farm floor swabs), 2.9 ± 0.9 (carcass swabs), 3.1 ± 1.0 (slaughterhouse floor swabs), and 3.3 ± 1.1 (market shop cutting board swabs) logCFU/cm2, whereas pork from the market had 3.4 ± 0.9 logCFU/g. Demonstrated high levels of Salmonella in the final product (pork at market) induces the potential health risks for the consumers. High values for E. coli indicates general poor hygiene along the chain. Appropriate hygiene practices and management are required to achieve better pork quality and reduce the risk for the consumer. These data will serve as inputs for health risk assessments related to pork consumption.